Derma-Hc, a New Developed Herbal Formula, Ameliorates Cutaneous Lichenification in Atopic Dermatitis - Nam, Yeon Kyung (Int J Mol Sci, 2021)
Atopic dermatitis (AD) is a chronic cutaneous disorder that is characterized by severe eczematous inflammation, swelling, and lichenification. Activation of T helper (Th)-22 cells by allergens leads to epidermal hyperplasia with hyperkeratosis at the chronic phase of AD. Derma-Hc is composed of five natural herbs with anti-AD effects, such as Astragalus membranaceus BUNGE, Schizonepeta tenuifolia Briq., Cryptotympana pustulata Fabr., Angelica sinensis Diels, Arctium lappa L. In this study, the ameliorative effect of Derma-Hc on cutaneous lichenification in 2,4-dinitrochlorobenzne (DNCB)-induced AD was investigated. The dorsal skin of mice was sensitized with DNCB to induce AD-like skin lesions. The dermatitis score and frequency of scratching were evaluated. Thickness of epidermis and dermis was measured by staining with H&E. In addition, infiltration of the mast cell was observed by staining with toluidine blue. Then, desmosomal cadherin, DSC1 was examined by immunofluorescence. Pathological mechanisms involved in lichenification were analyzed in AD-like skin lesions and TNF-α + IFN-γ-treated with human keratinocytes including keratinocyte differentiation genes and JAK1-STAT3 signaling pathway with IL-22 by RT-PCR and western blotting. Topical treatment of Derma-Hc improved AD-like symptoms such as dryness, edema and lichenefication and decreased the number of scratches. Histopathological analysis demonstrated that Derma-Hc significantly inhibited epidermal hyperplasia, hyperkeratosis, and mast cells infiltration. In addition, the level of DSC1 was highly expressed in the epidermis by Derma-Hc. Moreover, mRNA expression level of FLG, an epidermal differentiation complex gene, was recovered by Derma-Hc treatment. KLK5 and KLK7 were markedly reduced to normalize keratinocyte differentiation in dorsal skin tissues and human keratinocytes. On the other hand, Derma-Hc restored expression level of SPINK5. In addition, Derma-Hc inhibited IL-22 via the blockade of JAK1-STAT3 signal pathway. Taken together, Derma-Hc, a natural herbal formula, regulated keratinocyte differentiation and inhibited epidermal hyperplasia with hyperkeratosis. Therefore, Derma-Hc could be a promising candidate for treating chronic AD through modulating signaling of IL-22-associated skin lichenification.